Resídulo de bauxita: mapeamento da produção científica e tecnológica de sua aplicação em materiais cimentícios - Kanashiro, Mariana Kayoko (2018)
Bauxite residue (BR) is the major waste generated during alumina extraction from bauxite. The global average for the production of BR is estimated between 1 and 1.5 ton per ton of alumina. The most important process worldwide by which BR is generated is the Bayer process, which involves large amounts of sodium, turning this residue potentially toxic. Due to this, during the past decades, BR was considered an unusable waste. However, the storage of this high alkaline material, the difficulties and costs related to BR management have been motivating companies and research institutions to look for applications able to consume large amounts of BR. With this in mind, the civil construction industry, particularly cementitious materials industry, offers a promising option for BR utilization, since it consumes and produces large quantities of raw materials and products, respectively. Besides that, the cementitious materials industry is associated with a high environmental impact that could be diminished through the use of BR. Thus, the aim of the work herein is to engender useful information to guide decision makers and future researches through the analysis of scientific papers and patents indexed in the Web of Science and Derwent Innovations Index databases respectively. The software Vantage Point 5.0 was used to make bibliometric measures. These, in addition to technical information and reports from the industries were used as the basis for an analysis of advantages and disadvantages associated with the application of BR in the production of cementitious materials. Therefore, strategic issues and possible opportunities related to the use of BR for cementitious materials were identified and a deeper analysis was presented in the work herein.